Diagnostic Approach and Management of Solid Pancreatic Mass - Puspadina, Shafira; Simadibrata, Marcellus (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2022)
The pancreas is a complex organ in which a suspicious lesion can appear which can be benign or malignant. Clinical manifestation can guide the clinician to choose the appropriate tests such as autoimmune tests, tumor markers, imaging with ultrasonography (USG), computerized tomography (CT), magnetic resonance imaging (MRI), or magnetic resonance cholangiopancreatography (MRCP), and endoscopic or surgical tissue biopsy. Pancreatic nodule therapy is tailored to the nature of the nodule, etiology-appropriate therapy for benign nodules or surgery, chemotherapy, and radiotherapy for cancerous nodules. Knowledge of the diagnostic approach of pancreatic solid mass is important for clinician to make prompt and accurate treatment for patients and to prevent unnecessary examination or intervention.